Reaktivasi Paradigma Islam Wasathiyyah di Perguruan Tinggi Berdasar Konsultasi Tingkat Tinggi Ulama Dunia 2018 - Hasanah, Uswatun; Shunhaji, Akhmad; Zuhri, Saifuddin (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2020)
The paradigm of  wasathiyyah Islamic  is a form of Islamic understanding and practice, as well as an approach in contextualizing Islam in the midst of global civilization. The reactivation of the wasathiyyah Islamic paradigm was a response to various situations that attempted to divide the unity. This paradigm becomes important as a means of presenting the application of Islamic teachings that hold the principles of balance, justice and tolerance. This study aims to provide direction for Higher Education in developing the Islamic wasathiyyah paradigm. Through this research, the authors examined the wasathiyyah Islamic paradigm based on the Bogor Message which was produced at the 2018 World Ulama High Level Consultation (Summit) in Bogor. Bogor's message includes efforts to restore the Islamic wasathiyyah perspective as the center of Islamic teachings, both individually and collectively. One of the interesting messages to study is the commitment to reactivate the wasathiyyah Islamic perspective as a central Islamic teaching which includes seven main values, namely: tawassuth, i`tidâl, tasâmuh, syûrâ, islah, qudwah, and muwâthanah. This study uses a qualitative approach with a literature study method. The result shows the reactivation of the wasathiyyah Islamic paradigm in higher education, can be developed through the cultivation of the seven main values of wasathiyyah Islam as contained in the Bogor Message.